Crystallization and preliminary X-ray diffraction analysis of the catalytic subunit of ADP-glucose pyrophosphorylase from potato tuber - Binderup, K.; Watanabe, L.; Polikarpov, I; Preiss, J.; Arni, R. K. (Munksgaard Int Publ Ltd, 2000)
ADP-glucose pyrophosphorylase is the key regulatory enzyme in the biosynthesis of starch in plants and glycogen in bacteria. The enzyme from potato tuber is comprised of a regulatory subunit and a catalytic subunit and is present as a heterotetramer (alpha(2)beta(2)) the catalytic subunit from potato tuber (50 kDa) was crystallized in four different forms, two of which are suitable for structural studies. A tetragonal crystal form obtained in the presence of the substrate analog Cr-ATP diffracted to 2.2 Angstrom and belongs to space group P4(1) (or its enantiomorph), with unit-cell parameters a = b = 110.57, c = 190.14 Angstrom. A second crystal form obtained diffracted to 2.8 Angstrom and belongs to space group PZ, with unit-eel parameters a = 80.06, b = 138.84, c = 92.20 Angstrom, beta = 112.40 degrees. As this protein displays no significant homology to any currently known protein structure, a search for heavy-atom derivatives has been initiated.